There is time to be integrated: The relationship between SCM practices and organizational performance - The moderated role of competitive strategy - Xhavit Islami; Marija Topuzovska Latkovikj (Cogent Business & Management, 2022)
A perusal of the literature shows that a broad frame of references for organizational success is not adequately developed. Therefore, by taking an interdisciplinary approach with a relational perspective, this study takes an integrative and fresh approach toward illuminating the moderate role of competitive strategy in realizing the potential influence of supply chain management (SCM) practices on organizational performance of the manufacture organizations. Using the gathered data of 157 manufacturing organizations that operate in Kosovo, this study boosts the margins of the existing literature. The findings indicate a positive influence of SCM practices and competitive strategy on organizational performance. In addition, the findings also show that competitive strategy moderate the relationship between SCM practices and organizational performance. It highlights that differentiation strategy is necessary to increase the actual value of SCM practices and makes the organization flourish.
Keywords: 650; competitive strategy; manufacture industry; moderation effect; organizational performance; supply chain management practices